ANALISIS PENGELOLAAN DANA DESA DALAM PENANGGULANGAN PANDEMI COVID-19 - Aldehin Banoet; Meyulinda Aviana Elim; Alfred Tandirura Rantelobo (JAKA - Jurnal Jurusan Akuntasi, 2020)
Research on village fund management in tackling the Covid-19 pandemic (a case study in Kuanheun Village, West Kupang District, Kupang Regency, East Nusa Tenggara Province) aims to find out the process of managing village funds, especially at the budgeting stage (in the budgeting stage related to the preparation of the Village Income and Expenditure Budget. Fiscal Year 2020, changes to the Village Fund Budget for 2020, changes in priorities for the use of village funds in this case for the response to the Covid-19 Pandemic and the principles for drafting the Des Income and Expenditure Budget), the implementation stage (the implementation stage of village funds is related to the stages and requirements for distributing Village Funds In 2020, activities for handling Covid-19, Village Fund Direct Cash Assistance,and village financial administration) and the accountability stage in dealing with the Covid-19 pandemic (this accountability stage is related to the accountability report to be submitted to the Regent and the Village Consultative Body). This type of research uses a case study technique with a qualitative descriptive approach. The sample in this study amounted to 40 people consisting of village officials and the Kuanheun village community. Data collection was carried out by means of questionnaires, interviews and documentation which will be analyzed using qualitative descriptive methods in three stages, namely data reduction, data presentation, verification and conclusion. Based on the results of the analysis, it shows that the management of village funds at the budgeting stage has been carried out well but at the implementation stage and the accountability has not been fully carried out properly because at the implementation stage there are still activities which is not implemented according to what has been determined and at the accountability stage there is still no report made such as the first semester Realization of the Use of Village Funds Report.